Mapping Keynesian, Neoliberal and Social Investment ideals: The Swedish Social Democratic Party's welfare ideology from 1948 - 2014 - Leander,Cornelia (2018)
This thesis asks how developments in The Swedish Social Democratic Party’s welfare ideology over the past 70 years can be understood, using the conceptual lenses of Keynesian, Neoliberal and Social Investment welfare ideals. To answer this question, the thesis models a tailor-made seminal analytical tool; a code scheme of numerous operational indicators for Keynesian, Neoliberal and Social Investment welfare ideals. The tool conceptualizes the three welfare ideals as utterly distinct, and hence serve as a foundation for an ideal type analysis of The Swedish Social Democratic Party’s advocated welfare ideal. The tool is applied to 21 election manifestos, published by The Swedish Social Democratic Party between 1948 and 2014. Through a numerical content analysis, the thesis identifies operational indicators for each welfare ideal, and examines short- and long-run developments of the party’s expressed desires for the structure of the welfare system. In sum, the thesis concludes that the Keynesian ideal has been, and continues to be, most important for The Swedish Social Democratic Party. Yet, from 1948 to 1976/1979 this ideal was contested by the Social Investment ideal. From 1976/1979, the Neoliberal ideal has instead contested the Keynesian. Since the breakpoint, the Social Investment ideal has steadily increased its influence.
Keywords: Keynesianism; Neoliberalism; Social Investment; Welfare; Ideology; The Swedish Social Democratic Party